2011
DOI: 10.1037/a0021522
|View full text |Cite
|
Sign up to set email alerts
|

Blinded by the accent! The minor role of looks in ethnic categorization.

Abstract: The categories that social targets belong to are often activated automatically. Most studies investigating social categorization have used visual stimuli or verbal labels, whereas ethnolinguistic identity theory posits that language is an essential dimension of ethnic identity. Language should therefore be used for social categorization. In 2 experiments, using the "Who Said What?" paradigm, the authors investigated social categorization by using accents (auditory stimuli) and looks (visual stimuli) to indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
150
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 65 publications
12
150
0
4
Order By: Relevance
“…Implicit stereotypes are defined as strong cognitive associations between a stereotyped group and the attributes the members share (Blair and Banaji 1996). Research has shown that a person's accent also triggers stereotypes because ethnic background is often indicated by a particular accent (Rakić et al 2011), which might be especially important when it comes to ethnic minority students. Hence, the accent of ethnic minority students might be one component inherent in stereotypes, which, in turn, may result in lower language proficiency ratings and might be less prevalent in mathematical achievement.…”
Section: Discussionmentioning
confidence: 98%
“…Implicit stereotypes are defined as strong cognitive associations between a stereotyped group and the attributes the members share (Blair and Banaji 1996). Research has shown that a person's accent also triggers stereotypes because ethnic background is often indicated by a particular accent (Rakić et al 2011), which might be especially important when it comes to ethnic minority students. Hence, the accent of ethnic minority students might be one component inherent in stereotypes, which, in turn, may result in lower language proficiency ratings and might be less prevalent in mathematical achievement.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, data suggest that accents can be even more powerful indicators of category membership than visible ethnic features (Rakić, Steffens, & Mummendey, 2011). When members of nonstigmatized groups interact with stigmatized outgroups, they sometimes engage in linguistic divergence to reinforce their group memberships.…”
Section: Creating and Marking Group Boundariesmentioning
confidence: 99%
“…Ethnicity, as we understand it here, is not reducible to ancestry, genetics, skin color or race (Hirschman, 2004): Ethnicities are social categories that people attribute to themselves and each other (Turner et al, 1987). Although individuals may develop stable ethnic identities based on a variety of information and influences, ethnic categorizations in daily social interaction are likely to be much more fluid and informal (Jenkins, 1994;Okamura, 1981), based on contextual similarities and differences in observable (e.g., visible or audible) characteristics such as skin color or use of language (Maddox & Chase, 2004;Rakić et al, 2011). Thus, as suggested in SCT (Turner et al, 1987), we argue that being ethnically dissimilar in a group is a salient social situation that may differentially frustrate or satisfy these two motives.…”
Section: Demographic Dissimilarity and Strivings For Belonging And DImentioning
confidence: 99%
“…These criteria are often used to categorize others in initial social interactions (Maddox & Chase, 2004;Rakić et al, 2011). Moreover, in the context of Study 2 (i.e., diverse international business school in Britain), it is likely that students are identified with either a high status majority group (Anglo) or a low status minority group (non-Anglo) based on these two characteristics, rather than identified with more finely-grained subcategories (Guillaume et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation